Comparison of longissimus thoracis physical quality traits and the expression of tenderness-related genes between Goudali zebu breed and Italian Simmental × Goudali crossbreed. Issue 4 (2nd October 2018) - Saccà, Elena; Ojong Bessong, Willington; Corazzin, Mirco; Bovolenta, Stefano; Piasentier, Edi
Abstract: The aim of this trial was to compare some meat physical quality traits and the expression of some tenderness-related genes between Goudali (G, Bos indicus ) breed and Italian Simmental × Goudali (SimGoud, SG, Bos taurus x Bos indicus ) crossbreed. Ten G and 12 SG bulls, aged 31 ± 0.49 months, bred in the same farm and conditions in Western Highland Plateau Savannah of Cameroon were considered. Physical quality traits of longissimus thoracis (LT) muscle such as water losses, colour parameters and rheological properties were determined together with ultimate pH (pHu). The mRNA early post-mortem abundance of calpain-1 (Capn1), calpain-2 (Capn2), calpastatin (Cast), caspase 3 (Casp3), caspase 9 (Casp9), αB-crystallin (Cryab), heat shock proteins 27 (Hsp27), 40 (Hsp40) and 70 (Hsp70) was detected by qPCR. The Capn1, Cast, Hsp27 and Hsp70, early post-mortem protein content was determined by ELISA. The meat of G bulls had greater values of lightness ( p  < .05) and cooking loss ( p  < .05) than SG. The expression of Hsp70 in G was greater at mRNA ( p  < .05) level than SG. None of the other variables considered was significantly different between G and SG breeds. Whereas crossbreeding with Italian Simmental breed changed the colour and ameliorated the water retention capacity of G meat, tenderness and the expression of tenderness-related genes, both at mRNA and at protein level, were not significantly different between the pure local breed and the crossbreed. In comparison with pure Goudali, crossbreeding Goudali with Italian Simmental breed has a limited impact on meat traits in tropical conditions.